INNATE IMMUNITY IN INFANTS AND CHILDREN WITH INFECTION - Fatussonia, Sofia; Rizkinanda, Aulia; Farida, Meutia Dwi; Santi, Dwi Rukma (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2026)
The innate immune system serves as the first line of defense against pathogens, particularly in infants and children whose adaptive immune systems are not yet fully mature. Infants and children are highly susceptible to acute respiratory infections (ARI), diarrhea, and sepsis due to low antiviral cytokine production, a dominant Th2 response, and suboptimal immune cell maturation. This literature review aims to understand the role of innate immunity in determining susceptibility, disease course, and severity of infections in early childhood. The method used was a literature review of national and international journals published between 2020 and 2025, with thematic narrative analysis. The results of the study indicate that the innate immune system in children exhibits different activity compared to adults, with higher expression of antiviral genes and inflammatory mediators in the mucosa, but still low phagocytic function and production of certain cytokines. External factors such as nutrition, breast milk, vitamin D, and the microbiota also play a role in modulating the innate immune response. Understanding the mechanisms of innate immunity is crucial for developing strategies for preventing and managing infections in infants and children, including immunization, nutritional interventions, and probiotics, to reduce morbidity and mortality from infections in early life.